Enhancing The Sarawak Textile Museum Experience With Technology - Koid, Qian Hui (Universiti Malaysia Sarawak (UNIMAS), 2020)
As museum has shifted to audience- oriented, visitors’ experience has become the main concern of the museum. Increasing of visitors’ expectation causes the museum to face difficulty in sync with their curiosity and interests. Meanwhile, in this digital evolution era, technology offer a new opportunity for the museum to improve engagement and interactivity in order to meet the expectation of the visitors. The study focus on the Sarawak Textile Museum visitors’ experience. By combining the mobile technology and interactive display technology as a way to enrich the visitors’ experience yet increase Sarawak Textile Museum interactivity. Qualitative and qualitative research are carried out to collect the data. The findings is then analysed to understand visitors’ expectation and finally suitable technologies are proposed to develop in Sarawak Textile Museum.